Determinants of Green MSME Performance: The Mediation Role of Green Product Innovation - Warasniasih, Ni Made Sindy; Werastuti, Desak Nyoman Sri; Musmini, Lucy Sri (Dinasti Publisher, 2025)
This study aims to examine the influence of green transformational leadership, green entrepreneurial orientation, and green product innovation on the performance of green MSMEs, as well as the mediating role of green product innovation. The research is grounded in the growing importance of MSMEs in supporting sustainable development, particularly amid increasing demands for environmentally friendly products and business processes. The study focuses on woodcraft MSMEs in Gianyar Regency, Bali, employing a quantitative approach using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). Respondents were selected through purposive sampling, with a final sample of 209 participants. The findings reveal that green transformational leadership has a significant and positive direct effect on both green product innovation and green MSME performance. Similarly, green entrepreneurial orientation has a significant impact on green innovation, but not directly on MSME performance. Moreover, green product innovation is proven to play a significant mediating role in linking both leadership and entrepreneurial orientation with sustainable MSME performance. The implications of this study highlight the need for practitioners, policymakers, and scholars to strengthen green product innovation through environmentally oriented leadership and support for green entrepreneurship, ultimately enhancing the sustainable performance of MSMEs.